Uses and Gratification Theory Perspective: Assessing Technological Readiness and E-commerce Adoption as Drivers of MSME Performance (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to examine how the performance of micro, small, and medium enterprises (MSMEs) in the Special Region of Yogyakarta (DIY) is influenced by technology readiness and e-commerce adoption. E-commerce is a key element in the digital era that enhances productivity and expands market reach, yet low technology readiness often hinders its optimal implementation. Using a quantitative survey method, data were collected from 115 MSMEs across sectors such as food and beverage, creative industries, fashion, and interior/crafts. Multiple linear regression analysis was conducted with SPSS. The results reveal that technology readiness positively and significantly affects MSME performance by improving business effectiveness and efficiency. E-commerce adoption also contributes to performance, particularly through increased sales and wider market coverage. Overall, the findings highlight that technology readiness and e-commerce adoption are critical factors in strengthening MSME competitiveness in the digital era.
Keywords: Technology Readiness; E-Commerce Adoption; MSME Performance; E-commerce